The effect of weather on free space optics communication (FSO) under tropical weather conditions and a proposed setup for measurement - Zabidi, Suriza Ahmad; Al Khateeb, Wajdi Fawzi Mohammed; Islam, Md. Rafiqul; Naji, Ahmed Wathik (2010)
Free Space Optics communications (FSO) has attracted a lot of attention for a variety of applications in telecommunications field. The unlicensed, higher speed, broader and unlimited bandwidth, low cost solutions, and shortest deployment time frame are some of the drive to deploy FSO. However, weather attenuation has a big impact on the transmission line of FSO. There are a lot of studies and experiments have been done on FSO in the temperate climate region where the attenuation due to snow and fog are the two major problems in the deployment of FSO. However, there are no comprehensive study is done for the deployment of FSO in the tropical climate region where the rain and haze are present throughout the year. The objective of this paper is to produce analysis result of the different weather attenuations that have effect on FSO link. The parameters are attenuation due to geometric, molecular, atmospheric, rain, haze, and scintillation. The parameters are used to evaluate link availability of the FSO link. The result of the evaluation can provide more knowledge on the feasibility of FSO deployment under tropical weather condition especially for a long range link.